Production of 1,2,4-butanetriol from xylose by Saccharomyces cerevisiae through Fe metabolic engineering - Bamba, Takahiro; Yukawa, Takahiro; Guirimand, Gregory; Inokuma, Kentaro; Sasaki, Kengo; Hasunuma, Tomohisa; Kondo, Akihiko (Metabolic engineering, 2019)
1,2,4-Butanetriol can be used to produce energetic plasticizer as well as several pharmaceutical compounds. Although Saccharomyces cerevisiae has some attractive characters such as high robustness for industrial production of useful chemicals by fermentation, 1,2,4-butanetriol production by S. cerevisiae has not been reported. 1,2,4-butanteriotl is produced by an oxidative xylose metabolic pathway completely different from the xylose reductase-xylitol dehydrogenase and the xylose isomerase pathways conventionally used for xylose assimilation in S. cerevisiae. In the present study, S. cerevisiae was engineered to produce 1,2,4-butanetriol by overexpression of xylose dehydrogenase (XylB), xylonate dehydratase (XylD), and 2-ketoacid decarboxylase. Further improvement of the recombinant strain was performed by the screening of optimal 2-ketoacid decarboxylase suitable for 1,2,4-butanetriol production and the enhancement of Fe uptake ability to improve the XylD enzymatic activity. Eventually, 1.7 g/L of 1,2,4-butanetriol was produced from 10 g/L xylose with a molar yield of 24.5%. Furthermore, 1.1 g/L of 1,2,4-butanetriol was successfully produced by direct fermentation of rice straw hydrolysate. [Display omitted] •2-Ketoacid decarboxylase is a key enzyme for 1,2,4-butanetriol bio-production by S. cerevisiae.•Combination of BOL2 deletion and truncated TYW1 overexpression greatly improved iron-sulfur protein XylD activity in yeast.•An engineered yeast strain efficiently produced 1.1 g/L of 1,2,4-butanetriol from xylose enriched lignocellulosic hydrolysate.